Pengaruh Kinerja Pramusaji terhadap Operasional Hotel X di Bali - Yuliana, Yuliana (Binus Business Review, 2010)
Hospitality industry which is a service industry, inseparable from the role of process performance influence the waiter, where it plays an important role in the operational work which is part of the main elements to be a qualified waiter. Regarding the theories that support for the strengthening of this title is taken several interrelated theories regarding operational performance with the waitress at the Hotel X Bali. Research carried out by using descriptive correlation method by distributing questionnaires to employees and guests who later data processing using likertt scale. From the discussions that there will be value in the correlation (r) of 0.7263, which means there is a positive relationship between operational performance with the waiter, with a strong degree of correlation. Leverage rate coefficient (Determination) amounted to 52.75%, it can be said that the waitress who was influenced by the performance of the operational level of 52.75% and the remaining 47.25% influenced by other factors, such as motivation, working environment, and compensation.Â